Land Suitability Assessment with TOPSIS in the Agrarian Sector - Arvita Agus Kurniasari; Trismayanti Dwi Puspitasari; Pramuditha Shinta Dewi Puspitasari; Taufiq Rizaldi; I Gede Wiryawan (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
Sustainable development for agricultural productivity and environmental conservation necessitates proper land use and utilization planning. Land suitability analysis is a key tool in evaluating land potential by considering various aspects such as altitude, solar radiation, rainfall, humidity, temperature, wind speed and soil pH. Appropriate decision-making in this context requires processing and analysis of diverse datasets, often involving complex multi-criteria evaluations. Among the different methods used for making decisions based on multiple criteria, the Technique for Order Preference by Similarity to Ideal Solution, or TOPSIS, is special because it is easy to use, works well, and can handle both numbers and words as types of criteria. This research presents the development of a web-based Land Suitability Assessment with TOPSIS in the Agrarian Region of Bondowoso Regency. This system is built using PHP as a server-side language, utilizing web technology for wider accessibility and real-time user interaction supported by a Geographic Information System.. Using weather parameter data with a resolution of 0.50 x 0.50 (approximately 55 km x 55 km per grid), this Decision support system shows an accuracy level of 82.60% with comparative data for 2023. This system is expected to facilitate more effective and efficient decision-making in sustainable land use planning.